(untitled) (Communications in Mathematical Research, 2022)
We introduce a new infinite class of bipartite graphs, called jumped Wenger graphs, which has a similar structure with Wenger graphs. We give a tight upper bound of the diameter for these graphs and the exact diameter for some special graphs. We also determine the girth of the jumped Wenger graphs.